On the Origin of Hagionyms in North American French Surnames. (March 2015) - Picard, Marc
<x content-type="archive" xml:space="preserve">Abstract</x> Most surnames of French origin in North America were borne by migrants from various parts of France, so it is hardly surprising that the two sets should share many commonalities. One of these involves the existence of hagionymic family names, for example, Saint-Pierre, Saint-Jean, Sainte-Marie, and the like. A significant difference between them, however, is that the ones in present-day France invariably stem from surnames that were taken directly from hagiotoponyms, of which there were a great many, whereas the majority of those in North America originate from nicknames — the so-called dit names — of various types. Prominent among these were the numerous noms de guerre that discharged soldiers passed on to their descendants.